Elastic circular organic microcrystals prepared by photoinduced delamination - Chengde Ding; Baolei Tang; Liang Li; Panče Naumov; Hongyu Zhang (Nature Communications)
Abstract Circular organic crystals are essential as optically transducive components in flexible organic optoelectronics, yet this crystal habit is not easily obtained through traditional crystallization approaches. Here, we present a photoresponsive organic crystalline material that when exposed to ultraviolet or visible light, initially undergoes photoinduced bending, followed by photosalient effect and accompanied by delamination to elastic quasicircular microcrystals. Curvature analysis under different conditions confirms the controllability of this process. Light at 365 nm, 405 nm, and 445 nm generates microcrystals with high curvatures (11–12 mm−1), while 470 nm light produces lower curvature (5 mm−1), aligning with the absorption profile. Increasing the excitation power from 15 mW to 150 mW results in increase of the yield of microcrystals with high curvatures (10–20 mm−1) from 20% to 94%. This light-driven fabrication method provides a controlled and reproducible means of realizing rare crystal morphologies, highlighting the potential for exploring quantitative relationships between such morphologies and their unconventional optical properties.